PITUITARY METASTASIS UNVEILED FOLLOWING CRANIAL DIABETES INSIPIDUS UNMASKED BY STEROID - MK, Borhan; Tan, Florence HS; YC, Kuan (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Pituitary metastasis is uncommon and may occur via haematogenous or meningeal spread. The infundibulum or posterior lobe are commonly involved causing cranial diabetes insipidus (CDI). However, CDI may be masked in patients with glucocorticoid insufficiency due to concurrent hypopituitarism. RESULTS Case 1: A 54-year-old woman with stage 3 left breast invasive ductal carcinoma presented with blurring of vision and left 3rd nerve palsy. Brain CT reported left cavernous sinus mass. She was treated as cavernous sinus syndrome with oral prednisolone 30 mg BD. Shortly after, she complained of polydipsia and polyuria, with serum sodium of 154 mmol/L. Paired urine osmolality measurement was 190 mOsm/kg confirming diabetes insipidus. Her symptoms improved and serum sodium normalised after oral desmopressin. Brain MRI revealed thickened infundibulum and posterior pituitary leptomeningeal enhancement suggestive of metastasis. Hormonal workup revealed hypopituitarism. She received hormonal replacement and intrathecal chemotherapy. Case 2: A 64-year-old man with stage 3 nasopharyngeal carcinoma (NPC) on palliative chemotherapy was admitted for meningoencephalitis. On admission, he was septic and hypotensive, requiring inotropic support and was started on intravenous hydrocortisone. As his blood pressure improved, he developed polyuria up to 6 L/day. Endocrine consult was sought when his serum sodium increased from 144 mmol/L to 173 mmol/L. Urine specific gravity was 1.005 (reference value 1.015 to 1.025). He was started on SC desmopressin and IV hydration, with resolution of polyuria and hypernatremia. Brain MRI reported advanced NPC with extensive local infiltration including bilateral cavernous sinus and pituitary sella. Hormonal workup showed panhypopituitarism requiring thyroxine and hydrocortisone replacement. CONCLUSION Although rare, symptoms of diabetes insipidus in patients with malignancy should alert the physician for the possibility of pituitary metastasis. Failure to consider this diagnosis can lead to delay in treatment and complications.